Hubungan Digital Banking dan Kinerja Pelayanan Bank Syariah Terhadap Upaya Customer Retention di Masa Pandemi Covid-19 Pada Bank Syariah Indonesia (BSI) Kantor Cabang Perwakilan (KCP) Kota Serang - Yuyun Yuningsih; Suryani Suryani; Muhamad Fadli Azim (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
The purpose of this research is to find out and partialy and simultaneously prove the effect of digital banking and service performance on customer retention efforts. This study uses aquantitative approach. The data used in this study is primary data using multiple linear regression analysis, the sampling technique used was non-probability sampling or accidental sampling with 100 respondents. Based on simultaneous testing (Test F) also shows that the results of digital banking and service performance simultaneously heve a positive and significant effect on customer retention efforts.